The impact of exercises possession of the ball and attack the rapid development in the speed and accuracy of the tactical performance of the players of the Premier League football - Naji, Deyaa (Journal of Physical Education, 2015)
The evolution of the game of football came in conjunction with the development of scientific and practical aspects of training sports and research problem is in slow motion in fast attack and an end to the attack through tactical connectivity and scoring a goal when players Premier League football in Iraq and the aim of the research to design exercises for possession of the ball and quick attack to goal The most research sample my players the first team to Club students participating Premier League Iraqi football 2014-2015 season and the number (20) players were divided into two groups (10) experimental and (10) was an officer were applied exercises possession of the ball on the experimental group for eight weeks, with four training modules per week were the two test b 0 test speed and accuracy by linking tactical) and through the results show that exercise used on the experimental group contributed to the development of speed and accuracy to link tactical among a sample search experimental and recommended research use exercises possession and attack the rapid development of speed and accuracy to link tactical when players Iraqi Premier League football